2017
DOI: 10.18632/oncotarget.19882
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzyme USP5 promotes pancreatic cancer via modulating cell cycle regulators

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal solid tumors. With an overall five-year survival rate remaining below 6%, there is an explicit need to search for new molecular targets for therapeutic interventions. We undertook a barcode labelled short-hairpin (shRNA) library screen in pancreatic cancer cells in order to identify novel genes promoting cancer survival and progression. Among the candidate genes identified in this screen was the deubiquitinase USP5, which subsequent gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
5
39
0
Order By: Relevance
“…The pooled shRNA library is a valuable tool for gene screening. It has identified NQQ1 as a potential drug target for host‐directed tuberculosis therapy, ATP1A1 as a gene that regulates aurilide B cytotoxicity, and the deubiquitinating enzyme, USP5, which modulates cell cycle regulators . The shRNA screening system has also identified HIF1α as a TERT regulator using mouse ES cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled shRNA library is a valuable tool for gene screening. It has identified NQQ1 as a potential drug target for host‐directed tuberculosis therapy, ATP1A1 as a gene that regulates aurilide B cytotoxicity, and the deubiquitinating enzyme, USP5, which modulates cell cycle regulators . The shRNA screening system has also identified HIF1α as a TERT regulator using mouse ES cells …”
Section: Discussionmentioning
confidence: 99%
“…It has identified NQQ1 as a potential drug target for host-directed tuberculosis therapy, ATP1A1 as a gene that regulates aurilide B cytotoxicity, and the deubiquitinating enzyme, USP5, which modulates cell cycle regulators. [34][35][36] The shRNA screening system has also identified HIF1α as a TERT regulator using mouse ES cells. 37 In this study in a HCC cell line, we identified two genes, C15orf55 and C7orf43, as activators of TERT transcription through SP1 and YAP1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…USP5 have been reported as an oncoprotein in diverse cancers including myeloma 4 , non-small cell lung cancer 5 , hepatocellular carcinoma 6 , colorectal cancer 7 , ovarian cancer 8 and pancreatic cancer 9 . USP5 have been studied in the development of pancreatic cancer 9 , 10 . However, the role of USP5 in pancreatic cancer still needs to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…USP5 has been associated with tumorigenesis [15][16][17][18][19] , neurodegeneration [20][21][22] , and viral infections 23,24 . In addition, USP5 plays a role in regulation of ubiquitin levels in DNA damage repair 25 and stress granules 26 .…”
Section: Introductionmentioning
confidence: 99%